Pullet production and supply business development by women’s groups in selected kebeles of Dale pilot learning district (PLW): Experiences from IPMS - Yilma, K.; Tegegne, Azage; Hoekstra, Dirk; Yigzaw, M. (International Livestock Research Institute, 2012)
Shortage of pullet supply and high mortality of local chicks arising from diseases and inadequate feed were the main challenges identified through a rapid diagnostic survey on the poultry value chain in Dale. Accordingly, women group-based commercial pullet rearing as an input for smallholder poultry production was initiated by the Office of Agriculture and Rural Development (OoARD) and IPMS. To develop the program, a credit scheme was initiated using IPMS’s credit innovation funds. With assistance of OoARD, eighty women subdivided into five (village) groups, collectively purchased 4000 day-old chicks (50/woman) and other inputs such as feed, vaccines, hay box brooder and watering equipment. The women were trained and developed their skills through their group structures. The required vaccinations were also given by the women themselves under the auspices of the group structures. After 4–5 months, 3470 pullets survived and were kept by the women or sold to others for egg producers. Empirical results show that: i) the group approach helped to improve linkages, communication, and access to knowledge, technology, finance, inputs (day-old chicks and feed), veterinary service, and market; ii) the groups were able to successfully produce and supply pullets thus making an additional income of Ethiopian birr (ETB) 833/hh; iii) the approach stimulates growing demand for the 5 months-old pullets, especially by government/donor financed programs. While being technically and economically viable, the system requires institutional upgrading so as to ensure sustainability of input supply (chicks, feed and vaccine/drugs). The commitment shown by WoARD to provide technical backstopping in all aspects of poultry production also leaves much to be desired. These are crucial at least for the first few cycles, while more emphasis should be given to promoting improved local birds. As the follow-up studies on subsequent egg production showed, considerable attention needs to be paid to building the capacity of poultry farmers to engage in semi-commercial egg production, since egg production was still far below its potential. The study also shows that a difference of as high as 35% existed between egg production level by households who had purchased the pullets privately and households who had received the pullets through food security funded projects in Dale area.